2007
DOI: 10.1016/j.mod.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Early regionalization of the otic placode and its regulation by the Notch signaling pathway

Abstract: Otic neuronal precursors are the first cells to be specified and do so in the anterior domain of the otic placode, the proneural domain. In the present study, we have explored the early events of otic proneural regionalization in relation to the activity of the Notch signaling pathway. The proneural domain was characterized by the expression of Sox3, Fgf10 and members of the Notch pathway such as Delta1, Hes5 and Lunatic Fringe. The complementary non-neural domain expressed two patterning genes, Lmx1b and Iroq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 84 publications
4
81
0
Order By: Relevance
“…The forced expression of hJag1 in the dorsal domain of the otocyst close to the origin of the endolymphatic sac was ineffective in inducing Sox2 expression . Fate maps show that this domain derives from the dorsal and posterior otic cup (Abello et al, 2007;Bell et al, 2008;Brigande et al, 2000), which is devoid of neurosensory competence and does not express Sox2 (Neves et al, 2007) (Fig. 1).…”
Section: Research Articlementioning
confidence: 99%
“…The forced expression of hJag1 in the dorsal domain of the otocyst close to the origin of the endolymphatic sac was ineffective in inducing Sox2 expression . Fate maps show that this domain derives from the dorsal and posterior otic cup (Abello et al, 2007;Bell et al, 2008;Brigande et al, 2000), which is devoid of neurosensory competence and does not express Sox2 (Neves et al, 2007) (Fig. 1).…”
Section: Research Articlementioning
confidence: 99%
“…In Tbx1 -/-mice, the neurogenic region of the otic epithelium is expanded, the otocyst is small and the sensory patches do not form (Moraes et al, 2005;Raft et al, 2004;Vitelli et al, 2003;Xu et al, 2007). Our previous studies in chick revealed that Hairy1 (Hes1 homolog) is present in the non-neurogenic territory of the otic vesicle (Abello et al, 2007), suggesting that Hes1 might have an as yet unidentified role in neural patterning of the otic vesicle.…”
Section: Introductionmentioning
confidence: 98%
“…In an attempt to answer the first question, fate maps of the otic primordium have been performed in different species and at different stages (Brigande et al, 2000;Lang and Fekete, 2001;Kil and Collazo, 2001;Streit, 2002;Kozlowski et al, 1997;Satoh and Fekete, 2005;Abello et al, 2007; reviewed in Kil and Collazo, 2002). However, the results obtained so far fail to give a clear picture.…”
Section: Temporal Programme Of Otic Patterningmentioning
confidence: 99%